Bulk modulus evolution of thermoset resins during crosslinking: Is a direct and accurate measurement possible?. (February 2017) - Péron, Mael; Sobotka, Vincent; Boyard, Nicolas; Le Corre, Steven
The determination of the mechanical properties of thermoset resin and their evolution during transformation still represents a scientific issue in the composite materials community. A homemade apparatus named PvTα has recently been adapted to the measurement of neat resin bulk modulus evolution during cure and has been presented in a previous study. Several assumptions were used to directly obtain this value but they cannot be checked in situ. A multi-physic modelling of the system is proposed for this purpose in this paper. It accounts for the thermal, chemical and mechanical behaviours of the different components of the apparatus as well as their interactions during an experiment. This model is thoroughly validated thanks to several comparisons with experimental results. This study shows that the early assumptions are not verified during the whole cure in the case of RTM6 resin. It leads to 40% error in the bulk modulus estimation, thus making impossible a direct measurement of the resin bulk modulus using the simple protocol proposed by Nawab et al. A new procedure, which is based on the developed model, is proposed to improve the analysis accuracy.